Amaranthus palmeri--Palmer Amaranth - Pratap Devkota; Ramon Leon (EDIS)
Palmer amaranth has become one of the most troublesome weeds in the southeastern US due to its vigorous growth rate, high seed production, and development of resistance to herbicides from multiple modes of action. This 4-page publication illustrates characteristics of this weed to assist in accurate identification, proper management, and development of effective control strategies. Written by Sergio Morichetti, Jason Ferrell, and Pratap Devkota, and published by the UF/IFAS Agronomy Department, revised April 2020.